Unlocking the full potential of resistance training: a comparative analysis of low- and high-intensity effects on neurotrophic growth factors and homocysteine - Chongwen Zuo; Yi Yin; Zhiyang Zheng; Ren Mu; Yuxin Liang; Shan Wang; Chaoqun Ye (Discover Applied Sciences)
Abstract Objective Resistance training has been demonstrated an effective approach for preventing the cognitive function decline through physiological mechanisms; however, the effect of acute resistance training at different intensities on growth factor and homocysteine levels remains unclear. This study aimed to compare the impact of resistance training at varying intensities on peripheral neurobiological factors and homocysteine levels in young adults. Methods Twelve young male adults, predominantly engaged in various sports activities but without prior strength training experience, were recruited to participate in a randomized controlled cross-over trial. They implemented two different resistance training protocols: high intensity (HIRT, 12 repetitions at 80% 1RM) and low intensity (LIRT, 24 repetitions at 40% 1RM). Blood samples were collected at three time points: pre-training, post training, and after 30 min of rest to measure changes in serum lactate, serum brain-derived neurotrophic factor (BDNF), insulin-like growth factor 1 (IGF-1), vascular endothelial growth factor (VEGF), irisin, and plasma homocysteine (Hcy) levels. Results Both resistance training protocols significantly increased blood lactate and perceived exertion compared to pre-training (HIRT, p < 0.01; LIRT, p < 0.01), with higher levels observed in HIRT. Acute HIRT significantly elevated serum BDNF, IGF-1, and VEGF levels post training compared to LIRT (p < 0.05), while no difference was observed in irisin levels between the two protocols at any time point. Both training protocols significantly reduced plasma Hcy levels post training (p < 0.01) and maintained lower levels than pre-training and after 30 min of rest (p < 0.05), with no significant differences between the two protocols. Conclusions This study demonstrates that high intensity training appears to have a greater impact on specific neurobiological factors; however, regardless of intensity, resistance training can significantly decrease plasma homocysteine. Trial registration ClinicalTrials.gov ID: NCT06114550. Date of registration 01/30/2024.  https://clinicaltrials.gov/study/NCT06114550 .